Metabolic characterization of phosphate solubilizing microorganisms and their role in improving soil phosphate solubility, yield of upland rice (Oryza sativa L.), and phosphorus fertilizers efficiency - Fitriatin, Betty Natalie; Mulyani, Oviyanti; Herdiyantoro, Diyan; Alahmadi, Tahani Awad; Pellegrini, Marika (Frontiers in Sustainable Food Systems, 2022)
Some soil microbes have the ability to increase soil P availability through P dissolution known as phosphate solubilizing microbes (PSM) . These microbes are able to produce growth regulatory compounds to increase plant growth. The purpose of this research were to study the characterization of PSM and to determine the effect of PSM application on P solubilize, soil phosphatase activity, and yield of upland rice. The stages of the research was carried out the characterization of rhizos isolates to analyze the production of organic acids, phosphatase enzymes and phytohormones. The green house experimental design used a factorial randomized block design consisting of two factors with three replications. The first factor were PSM isolates consisting of four levels i.e.: without microbes, P-solubilizing bacteria (Burkholderia sp.), P-solubilizing fungi (Penicillium sp.), and mixture of Burkholderia sp.with Penicillium sp. While the second factor were the dose of P fertilizer (super phosphate) which consists of four levels i.e. 0, 50, 75 and 100 kg P ha-1. The characterization of PSM has been shown that PSM produce organic acids i.e. : lactate acid, oxalate acid, citric acid, acetate acid, phytohormone (IAA) and phosphatase enzyme. The results of pot experiment showed that inoculation of PSM increased the available P and soil phosphatase, P content of plant, decreased of soil organic P and yield of upland rice. Mixed inoculants of phosphate solubilizing bacteria and fungi gave better effect for increasing available P, phosphatase activity, P content of plant and upland rice yields. The application of P fertilizer with a dose of 75 kg P ha-1 had a better effect on available P, phosphatase activity and upland rice yields.